The influence of chemical reaction parameters on the interaction of thermal, diffusion and mechanical waves under surface treatment by a particle beam - Parfenova, Elena Sergeyevna; Knyazeva, Anna Georgiyevna (Computational Continuum Mechanics, 2021)
A coupled non-isothermal model of the penetration process of a material into a target surface under conditions of surface treatment with a particle beam is presented. The model takes into account the interaction of impurity diffusion, heat propagation, mechanical disturbances and the chemical reaction between the introduced impurity and the substrate material. The problem is formulated in terms of dimensionless variables. All model parameters and the range of numerical values are given. The problem is solved numerically using an implicit symmetric difference scheme of the second order approximation in time and coordinates. The solutions are obtained for different time intervals determined by the characteristic pulse action time and relaxation times for diffusion and thermal conductivity. It has been established that the interrelation of processes of different scales leads to the appearance of distortions on strain and stress waves, and the distributions of temperature and impurity concentration acquire a wave character. The formation of chemical compound leads to a decrease in the concentration of impurities and to an increase in temperature, stresses and deformation. It is shown that the chemical reaction at low heat generation proceeds only as long as the temperature increases due to the introduced energy. It has been found that, at slow formation of the product in the reaction, the chemical interaction practically does not affect the propagation of temperature, deformation, stresses and impurity concentration.
Keywords: coupled model; particle beam; wave propagation; nonlinear effects; elastic stresses; diffusion; heat conduction; relaxation of heat flux; relaxation of mass flux; chemical reaction